Revitalisasi Kegiatan Keagamaan untuk Penguatan Karakter Religius Siswa di MI Nurul Mun’im Karanganyar - Iqbal, Muhammad; Astutik, Astutik (Moderasi : Journal of Islamic Studies, 2024)
Moral degradation among youth in Indonesia, exacerbated by digital disruption and globalization, necessitates an urgent reevaluation of character education within formal schooling. This study explores the implementation of religious activities as a strategy to strengthen students’ religious character at MI Nurul Mun’im Karanganyar, a primary Islamic school located in a coastal and culturally diverse region. Employing a qualitative case study approach, data were collected through semi-structured interviews, participatory observation, and documentation. The findings reveal six interrelated strategies in religious activity implementation: curriculum integration, religious habituation, direct worship training, extracurricular Islamic programs, teacher role modeling, and behavioral instruction. These strategies are supported by strong school leadership, teacher cohesion, parental involvement, and adequate facilities. However, challenges remain, including inconsistent student discipline, varied religious support from families, and limitations in teacher capacity and documentation. The study underscores the significance of a holistic and contextual approach to character education, where religious activities are not merely ritualistic but serve as transformative pedagogical practices. The implications of this research provide practical recommendations for Islamic educational institutions in similar sociocultural contexts.